Genome-wide analysis of HSP20 gene family and expression patterns under heat stress in cucumber (Cucumis sativus L.) - Huang, Junjun; Hai, Zhaoxin; Wang, Ruoyi; Yu, Yuanyuan; Chen, Xin; Liang, Weihong; Wang, Huahua (Frontiers in Plant Science, 2022)
Cucumber is an important vegetable in China, and its yield and cultivation area are among the largest in the world. Excessive temperatures lead to high-temperature disorder in cucumber. Heat shock protein 20 (HSP20), an essential protein in the process of plant growth and development, is a universal protective protein with stress resistance. HSP20 plays crucial roles in plants under stress. In this study, we characterized the HSP20 gene family in cucumber by studying chromosome location, gene duplication, phylogenetic relationships, gene structure, conserved motifs, protein-protein interaction (PPI) network, and cis-regulatory elements. A total of 30 CsHSP20 genes were identified, distributed across 6 chromosomes, and classified into 11 distinct subgroups based on conserved motif composition, gene structure analyses, and phylogenetic relationships. According to the synteny analysis, cucumber had a closer relationship with Arabidopsis and soybean than with rice and maize. Collinearity analysis revealed that gene duplication, including tandem and segmental duplication, occurred as a result of positive selection and purifying selection. Promoter analysis showed that the putative promoters of CsHSP20 genes contained growth, stress, and hormone cis-elements, which were combined with protein-protein interaction networks to reveal their potential function mechanism. We further analyzed the gene expression of CsHSP20 genes under high stress and found that the majority of the CsHSP20 genes were upregulated, suggesting that these genes played a positive role in the heat stress-mediated pathway at the seedling stage. These results provide comprehensive information on the CsHSP20 gene family in cucumber and lay a solid foundation for elucidating the biological functions of CsHSP20. This study also provides valuable information on the regulation mechanism of the CsHSP20 gene family in the high-temperature resistance of cucumber.